Применение метода граничных элементов для численного решения линейных краевых задач в областях с сильно сегментированной границей - Бразалук, Юлия Владимировна (НТУ "ХПИ", 2019)
В настоящей работе метод граничных элементов был применен к решению краевых задач для уравнения Лапласа в плоской области с сильно сегментированной границей. Особое внимание было уделено точности численного решения, которая исследовалась путем численного эксперимента на специально подобранных тестовых задачах, имеющих аналитические решения в квадратурах. Было реализовано два алгоритма метода граничных элементов: традиционный с решением системы линейных алгебраических уравнений методами гауссовского исключения, и итерационный, при этом в итерационном алгоритме использовались функции Грина или их вычислительные аналоги. Результаты работы могут быть использованы при создании специализированного программного обеспечения соответствующего назначения.

One of the most serious problems of modern numerical analysis is boundary-value problem solution in domains of complex geometrical shapes. Such problems are proved especially difficult for the domains with strongly segmented boundary, which meansthat the boundary is divided into isolated pieces. Such situations are specific for heterogeneous media. In such situations local approximation methods have to deal with the insuperable difficulties such as constructing computational grid and subsequent solving rather sophisticated systems of linear algebraic equations. The methods of global approximations and, first of all, methods of computational potential theory do not have similar difficulties, nevertheless they have to overcome a lot of problems. Boundary element method is applied in thepresent work to solve boundary-value problems for Laplace equations in plane domain with strongly segmented boundary. Special attention in the work was paid to accuracy of numerical solutions. The accuracy is investigated by a numerical experiment using specially selected test problems, which have the known analytical solutions in quadrature. Two boundary element algorithms are implemented. The first one is the traditional approach with Gauss elimination algorithm for solving linear algebraic equation system. The second one is an iterative approach with possible using of Green’s functions or their computational analogs in the iterative procedure. The results obtained in the work can be applied for creating specialized software of corresponding purposes.
Boundary element method application to numerical solving of linear boundary-value problems in domains with strongly segmented boundary
Keywords: уравнение Лапласа; погрешность; тестовая задача; функция Грина; Laplace equation; error; test problem; Green’s function